Nutritional Characteristics of White Bread Banana Horn Flour (Musa Paradisicia) with the Addition of Fragrant Pandan Leaf Extract (Pandanus Amaryllifolius-Roxb) as an Alternative Source of Carbohydrates and Protein - Ajeng Kusumawardani; Rinten Anjang Sari; Astri Ayu Novaria (Formosa Journal of Sustainable Research, 2023)
Indonesia is one of the countries that uses white bread as a substitute for rice or as a snack. White bread is a food product made from wheat flour which is then given yeast and baked. This research used experimental research with a completely randomized design (CRD) with 5 treatments and 3 repetitions. Proximate test testing for water content, ash content, protein content, fat and carbohydrate content and acceptability test. The results of the nutrient content test for white bread, banana flour with fragrant pandan leaf extract, are the most preferred and good in white bread products, namely in the R3 treatment with high levels of results. air 25.79%, ash content 1.378%, protein content 7.88%, fat content 4.218% and carbohydrate content 60.72%. And the most favorable hedonic test results and hedonic quality were the R3 white bread treatment with the substitution of banana horn flour with the addition of fragrant pandan leaf extract, which stated that there was no real difference and no further tests were carried out. White bread with the substitution of horn banana flour with the addition of fragrant pandan leaf extract was declared to have no real difference and no further testing was carried out